1 - Colour-line: The Petrifaction of Racialization and Alterity at the University of Stellenbosch - Fazil Moradi (Journal of Higher Education in Africa, 2010)
This paper investigates ‘black’ (minority) student experiences and living conditions at an Afrikaans-speaking historically white university, the University of Stellenbosch (SU). It is an empirical attempt to unearth the present conditionality of minority students that make up 14 per cent of the enrolled students at SU. Thus it involves social (under-)development and is a move away from the individual as unit of analysis per se and includes assessment of the social processes that condition a racialized dividing-line between different groups and at once prolong group affiliation/belonging. The main focus is on the following themes essential to the dispute on educational transformation in South Africa: racialized skin colour and stereotypes, access to language and education, and segregated spaces and economic reality. I apply qualitative research interview and utilize the post- colonial approach to argue that minority students constantly encounter the reinstatement of a racialized system of difference that excludes and positions them as marginalized subjects. It is argued that these experiences are due to the corporeal schema and cultural characteristics that delineate membership at SU, which make minority students more resistant and at once more ambivalent about the pursuit of education as a self-realization process, and more importantly an investment for future life, which constitute the main force for almost all of the minority students.